The discursive construction of national identity - Wodak, Ruth 1950- (Edinburgh University Press, 2009)
How do we construct national identities in discourse? Which topics, which discursive strategies and which linguistic devices are employed to construct national sameness and uniqueness on the one hand, and differences to other national collectives on the o